320 Roseomonas, an Emerging Opportunistic Pathogen. (11th January 2018) - Hassan, Muhammad Masood; Khan, Farhan; Naab, Tammey
Abstract: Roseomonas, an aerobic, nonfermentative, Gram-negative coccobacillus, has been reported as a rare cause of bacteremia. It is an organism with low pathogenic potential that can cause serious infections, often in immunocompromised patients. Roseomonas is found in the environment, including the soil, water, and air. Roseomonas is an emerging opportunistic pathogen with infection probably related to skin microbiota. We report a case of a 26-year-old African-American man who presented with low back pain, headache, fever, cough with hemoptysis, and dizziness. The patient denied any recent travel and the use of recreational drugs. Urine drug screen was negative. Glasgow coma score was 15/15. Significant lab findings were potassium 3.4 mEq/L and platelet count 131/uL. WBC count was normal, but neutrophils comprised 82.2% and lymphocytes 5.7 %. Chest X-ray revealed minimal peribronchial wall thickening. Head CT scan was normal. Two sets of blood culture revealed plump Gram-negative coccobacilli. Roseomonas on sheep blood agar showing nonhemolytic, pale pink, mucoid, almost runny colonies after 72-hour incubation, which were beta lactamase positive. Influenza antigen was also positive. The clinical manifestations of the patient might be due to Roseomonas spp infection or coinfection with both organisms. In immunocompetent patients, mild infections of Roseomonas spp with nonspecific symptoms have been reported. This case study shows the identification of a rare low-grade bacterial pathogen.